Pulsed field ablation selectively spares the oesophagus during pulmonary vein isolation for atrial fibrillation. Issue 9 (7th May 2021) - Cochet, Hubert; Nakatani, Yosuke; Sridi-Cheniti, Soumaya; Cheniti, Ghassen; Ramirez, F Daniel; Nakashima, Takashi; Eggert, Charles; Schneider, Christopher; Viswanathan, Raju; Derval, Nicolas; Duchateau, Josselin; Pambrun, Thomas; et al.
Abstract: Aims: Extra-atrial injury can cause complications after catheter ablation for atrial fibrillation (AF). Pulsed field ablation (PFA) has generated preclinical data suggesting that it selectively targets the myocardium. We sought to characterize extra-atrial injuries after pulmonary vein isolation (PVI) between PFA and thermal ablation methods. Methods and results: Cardiac magnetic resonance (CMR) imaging was performed before, acutely (<3 h) and 3 months post-ablation in 41 paroxysmal AF patients undergoing PVI with PFA ( N = 18, Farapulse) or thermal methods ( N = 23, 16 radiofrequency, 7 cryoballoon). Oesophageal and aortic injuries were assessed by using late gadolinium-enhanced (LGE) imaging. Phrenic nerve injuries were assessed from diaphragmatic motion on intra-procedural fluoroscopy. Baseline CMR showed no abnormality on the oesophagus or aorta. During ablation procedures, no patient showed phrenic palsy. Acutely, thermal methods induced high rates of oesophageal lesions (43%), all observed in patients showing direct contact between the oesophagus and the ablation sites. In contrast, oesophageal lesions were observed in no patient ablated with PFA (0%, P < 0.001 vs. thermal methods), despite similar rates of direct contact between the oesophagus and the ablation sites ( P = 0.41). Acute lesions were detected on CMR on the descending aorta in 10/23 (43%) after thermal ablation, and in 6/18 (33%) after PFA ( P = 0.52). CMR at 3 months showed a complete resolution of oesophageal and aortic LGE in all patients. No patient showed clinical complications. Conclusion: PFA does not induce any signs of oesophageal injury on CMR after PVI. Due to its tissue selectivity, PFA may improve safety for catheter ablation of AF. Graphical Abstract: